COMMUNITY EMPOWERMENT THROUGH SUKA MULIA WASTE BANK IN IMPROVING HOUSEHOLD ECONOMIC WELFARE IN PEMATANG JOHAR VILLAGE - LABUHAN DELI DISTRICT - Sari, Nurul Wilda; Madya, Efi Brata (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The issue of suboptimal waste management often leads to environmental pollution and neglects the economic potential of household waste. Amidst this issue, the waste bank program emerges as an innovative solution that not only reduces waste volume but also empowers the community economically. This study aims to analyze the role of the Suka Mulia Waste Bank in improving the economic welfare of the community in Pematang Johar Village, Labuhan Deli District. The study uses a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The results show that the waste bank plays a significant role in enhancing community welfare through several mechanisms. First, it provides economic incentives such as waste payments, waste savings, and programs to exchange waste for basic needs. Second, it opens new business opportunities through training in recycling waste into economically valuable products such as eco-bricks, paving blocks, liquid fertilizer, and handicrafts. Third, it expands access to social assistance and public services through programs such as paying BPJS premiums, land taxes (PBB), and even school fees from waste savings. This program also fosters environmental awareness and a household-level culture of waste sorting. The success of the waste bank’s implementation is supported by active community participation, village government support, and the involvement of external institutions. Therefore, the waste bank program must continue to be developed with cross-sectoral support so that its benefits can be widely felt, sustainable, and become a model of environmentally based community empowerment.